CLINICAL AND LABORATORY PARAMETERS INFLUENCING VARICOCELECTOMY SUCCESS IN THE TREATMENT OF SUBFERTILE MEN - Shomarufov Azizbek Bahodir ugli; Abbosov Shukhrat Anvarovich (Galaxy International Interdisciplinary Research Journal, 2024)
Varicocele, a condition in which the veins within the scrotum become enlarged, has been studied for over a thousand years. However, there are still many debates surrounding its treatment, particularly with regard to its limited efficacy in improving fertility in men from infertile couples. There are various clinical and laboratory factors that may impact the success of varicocele repair. Recent analysis suggests that evidence on the predictors of varicocele repair efficacy remains controversial. However, initial semen parameters such as sperm concentration and/or TMSC may be relatively important in predicting the success of varicocelectomy in treating male infertility.